The genome of Tripterygium wilfordii and characterization of the celastrol biosynthesis pathway - Tianlin Pei (GigaScience Press, 2021)
Tripterygium wilfordii is a vine from the Celastraceae family that is used in traditional Chinese medicine (TCM). The active ingredient, celastrol, is a friedelane-type pentacyclic triterpenoid with putative roles as an antitumor, immunosuppressive, and anti-obesity agent. Here, we report a reference genome assembly of T. wilfordii with high-quality annotation using a hybrid sequencing strategy. The total genome size obtained is 340.12 Mb, with a contig N50 value of 3.09 Mb. We successfully anchored 91.02% of sequences into 23 pseudochromosomes using high-throughput chromosome conformation capture (Hi–C) technology. The super-scaffold N50 value was 13.03 Mb. We also annotated 31,593 structural genes, with a repeat percentage of 44.31%. These data demonstrate that T. wilfordii diverged from Malpighiales species approximately 102.4 million years ago. By integrating genome, transcriptome and metabolite analyses, as well as in vivo and in vitro enzyme assays of two cytochrome P450 (CYP450) genes, TwCYP712K1 and TwCYP712K2, it is possible to investigate the second biosynthesis step of celastrol and demonstrate that this was derived from a common ancestor. These data provide insights and resources for further investigation of pathways related to celastrol, and valuable information to aid the conservation of resources, as well as understand the evolution of Celastrales.